Bax-induced apoptosis shortens the life span of DNA repair defect Ku70-knockout mice by inducing emphysema. Issue 12 (June 2016) - Matsuyama, Shigemi; Palmer, James; Bates, Adam; Poventud-Fuentes, Izmarie; Wong, Kelvin; Ngo, Justine; Matsuyama, Mieko
Cells with DNA damage undergo apoptosis or cellular senescence if the damage cannot be repaired. Recent studies highlight that cellular senescence plays a major role in aging. However, age-associated diseases, including emphysema and neurodegenerative disorders, are caused by apoptosis of lung alveolar epithelial cells and neurons, respectively. Therefore, enhanced apoptosis also promotes aging and shortens the life span depending on the cell type. Recently, we reported that ku70 − / − bax − / − and ku70 − / − bax +/ − mice showed significantly extended life span in comparison with ku70 − / − bax +/+ mice. Ku70 is essential for non-homologous end joining pathway for DNA double strand break repair, and Bax plays an important role in apoptosis. Our study suggests that Bax-induced apoptosis has a significant impact on shortening the life span of ku70 − / − mice, which are defective in one of DNA repair pathways. The lung alveolar space gradually enlarges during aging, both in mouse and human, and this age-dependent change results in the decrease of respiration capacity during aging that can lead to emphysema in more severe cases. We found that emphysema occurred in ku70 − / − mice at the age of three-months old, and that Bax deficiency was able to suppress it. These results suggest that Bax-mediated apoptosis induces emphysema in ku70 − / − mice. We also found that the number of cells, including bronchiolar epithelial cells and type 2 alveolar epithelial cells, shows a higher DNA double strand break damage response in ku70 KO mouse lung than in wild type. Recent studies suggest that non-homologous end joining activity decreases with increased age in mouse and rat model. Together, we hypothesize that the decline of Ku70-dependent DNA repair activity in lung alveolar epithelial cells is one of the causes of age-dependent decline of lung function resulting from excess Bax-mediated apoptosis of lung alveolar epithelial cells (and their progenitor cells).